Methodical interpretations on the organization of independent educational classes in the subject of painting - Muhammadiyeva Zarina Bahodirovna; Sadatov Chori Xolmurodovich (Research Parks Publishers, 2020)
In the article, recommendations were developed on the planning of Independent Education of students on the subject of painting, its organization and creating the necessary conditions for this, as well as teaching the students to study more in classrooms, showing ways of obtaining knowledge and organizing independent educational sessions